STRATEGIC DECISION MAKING FOR ENHANCING PROFITABILITY USING SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE (SMART) : THE CASE OF LB RESTAURANT - Nur Muhammad Rifaat; Utomo Sarjono Putro (LPPM STIE Muhammadiah Bandung, 2025)
Many restaurant businesses struggled to survive and went bankrupt during the COVID-19 period. LB Restaurant, a food and beverage (F&B) business based in Bandung, Indonesia, faced financial challenges after the COVID-19 pandemic. These challenges arose due to unstable profit growth and increasing, uncontrolled operational costs, which continuously eroded the company’s earnings and resulted in minimal profits. This study aims to identify strategies to improve the profitability of LB Restaurant by utilizing SWOT (Strengths, Weaknesses, Opportunities, Threats) and TOWS Analysis to assess the restaurant’s internal and external factors, based on Common-size Analysis and Profitability Ratio Analysis, the VRIO (Valuable, Rare, Inimitable, Organized) Framework, Value Chain Analysis, and Michael Porter’s Five Forces. Using the SMART method, five alternative strategies: revenue diversification and cost control, maximizing partnerships, digitally enhanced customer retention and social media-driven upselling, financial buffer and contractual safeguards, and streamlined peak-hour operations, were analyzed and prioritized according to the criteria of profit potential, cost potential, customer retention potential, and implementation challenges for each strategic alternative.